Investment return for Gala apple cultivar using two planting densities - Kreuz, Carlos Leomar (Pesquisa Agropecuaria Brasileira, 2002)
The present study was carried out to analyse economic performances of Gala apple orchards at different planting densities. Two orchard densities (1,000 and 3,378 plants/ha) were evaluated in an orchard near Fraiburgo, SC, Brazil. The use of both planting densities resulted in the same internal rate of return (approximately 1.6% a month). It is suggested to use a lower planting system, once it requires less capital. Unit cost also remained the same for both planting densities used in this study.